Impact of Foreign Capital Inflow on Economic Growth in Nigeria - Kutu , Augustine Adebayo; Ohonba, Abieyuwa (Journal of Ecohumanism, 2024)
The study examines the impact of foreign capital inflows on economic growth in Nigeria between 1984 to 2020. Four core channels of foreign capital inflows were adopted which consist of foreign direct investment (FDI), official development assistance (ODA), and remittances (REM) as the explanatory variables and GDP as the dependent variable. The overall finding revealed that foreign capital inflows have a long-run impact on economic growth in Nigeria except for official development aids. Specifically, the ARDL long-run result revealed that FDI and REM exert strong positive effects on GDP. This implies that FDI and REM are key factors that promote economic growth in Nigeria. Granger causality shows a uni-directional relationship running only from remittance to GDP, implying that remittance is a predictor of economic growth in Nigeria. Interestingly, a bi-directional causal effect exists between FDI and GDP (both are influencers of each other). This generally implies that international capital inflow is one major promoter of economic growth in Nigeria. Therefore, the study recommends that Nigeria should pursue workable foreign investment policies that are geared towards attracting inflows of foreign capital which is expected to help generate meaningful economic growth by improving the pace of industrialization and creation of more job opportunities for the teeming youths.